factorice 9square-4bsquare-6a+1
Answers
Answered by
0
9a^2 - 4b^2 - 6a +1
=> 9a^2 - 6a + 1 - 4b^2
=> (3a)^2 - 2(3a)(1) + (1)^2 - (2b)^2
=> (3a-1)^2 - (2b)^2
=> (3a-1-2b) (3a-1+2b)
=> 9a^2 - 6a + 1 - 4b^2
=> (3a)^2 - 2(3a)(1) + (1)^2 - (2b)^2
=> (3a-1)^2 - (2b)^2
=> (3a-1-2b) (3a-1+2b)
anu475:
please explain in simple way
Answered by
0
9a^2 - 4b^2 - 6a +1
=> 9a^2 - 6a + 1 - 4b^2
=> (3a)^2 - 2(3a)(1) + (1)^2 - (2b)^2
=> (3a-1)^2 - (2b)^2
=> (3a-1-2b) (3a-1+2b)
hope it helped ⚡
braínlíest please ❤️
Similar questions